Sikap guru terhadap penggunaan komputer dalam pengurusan sekolah di daerah Sandakan - Syamsul Bahri, Andi Mapiare (2011)
The purpose of the study was to identify the attitude of teachers regarding the usage of computers in primary school management in the district of Sandakan, Sabah. The study was a 4-point survey method and employed questionnaire approach for data gathering. A set of instrument namely Computer Attitude Scale (Loyd & Loyd, 1985) was used to measure 4 dimensions of attitude such as computer anxiety, computer confidence, computer liking and computer usefulness in school management. The research sample consisted of 320 teachers from 64 primary schools in the district of Sandakan who were selected through a stratified random sampling process. The data was analysed by using Statistical Package for Sosial Science (SPSS) version 12.0. Descriptive statistics such as means, frequencies and percentages were the results from the analysis. Inferential statistics had analyzed T-test, ANOVA and correlations coefficients of the variables. The overall findings revealed that teachers had shown moderately positive attitude towards computer usage. The gender and training factors did not affect the usage of computer among respondents. The findings also showed that there were significant differences between age, accessibility, and skills factors with teacher attitude. Several recommendations for improvement were put forward such as to involve secondary school teachers as the research samples, conduct extensive studies in other districts in Sabah and to differentiate the attitude of rural and urban teachers.